Exploring antenatal care experiences amongst pastoralist communities in Kenya: a focused ethnographic study - Barako, Talaso Dulacha (2021)
Background: Antenatal care (ANC) is a very important component of maternity care to ensure a healthy pregnancy and safer childbirth, particularly in areas where maternal health is poor. However, whilst progress has been made to reduce maternal deaths and increase ANC coverage globally, challenges remain in bringing ANC to specific remote or rural communities, such as pastoralist communities in sub-Saharan Africa. This PhD study focuses on ANC amongst a semi-nomadic pastoralist community in one part of Kenya. Pastoralist communities are herders of domesticated livestock, though some incorporate agriculture into pastoralism. Nomadic pastoralists organise their lives around the needs of their animals, which is characterised by migration depending upon weather patterns. In Kenya, there are at least 5.6 million rural pastoralists. Existing reports show that pastoralist communities tend to lack access to services and face long-standing marginalisation, poverty, and vulnerability. Further, in some African countries, including Kenya, gender norms mean that pastoralist women face double marginalisation in terms of decision making, access to education, and healthcare services. The research setting is Marsabit County in Kenya where 80% of the population is pastoralist. Marsabit has the fourth highest maternal mortality and morbidity rates in Kenya at 1,125 per 100,000 live births, and the highest teenage pregnancy rates. Pastoralist women’s access to and use of ANC services in Kenya has not been studied previously.